2021
DOI: 10.3390/molecules26020314
|View full text |Cite
|
Sign up to set email alerts
|

Noticeable Quantities of Functional Compounds and Antioxidant Activities Remain after Cooking of Colored Fleshed Potatoes Native from Southern Chile

Abstract: The effect of cooking on the concentrations of phenolic compounds and antioxidant activities in 33 colored-fleshed potatoes genotypes was evaluated. The phenolic profiles, concentrations, and antioxidant activity were evaluated with a liquid chromatography diode array detector coupled to a mass spectrometer with an electrospray ionization interface (HPLC-DAD-ESI-MS/MS). Eleven anthocyanins were detected; in the case of red-fleshed genotypes, these were mainly acyl-glycosides derivatives of pelargonidin, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 38 publications
(29 reference statements)
2
16
1
Order By: Relevance
“…(2012) . These data are also consistent with those of other studies, which reported that colored potatoes have high concentrations of anthocyanins, reaching 1200 mg kg -1 FW ( Ruiz et al., 2018 ; Ercoli et al., 2021 ; Alarcón et al., 2022 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…(2012) . These data are also consistent with those of other studies, which reported that colored potatoes have high concentrations of anthocyanins, reaching 1200 mg kg -1 FW ( Ruiz et al., 2018 ; Ercoli et al., 2021 ; Alarcón et al., 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…Chilean native potatoes with the highest TPC and anthocyanin content possess mostly blackish skin and/or purple flesh, indicating the traditional accessions with blackish skin and dark purple flesh, and these results are consistent with those reported by Ah-Hen et al (2012). These data are also consistent with those of other studies, which reported that colored potatoes have high concentrations of anthocyanins, reaching 1200 mg kg -1 FW (Ruiz et al, 2018;Ercoli et al, 2021;Alarcoń et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…In genotypes lacking pigmentation, such as VR808, the main components with antioxidant capacity are the carotenoids of the xanthophyll family 40 . In coloured genotypes, it has been reported that the most abundant anthocyanins include pelargonidin, peonidin, petunidin and malvidins, glycosylated and acylated with hydroxylated aromatic acids, 41 whereas in red‐fleshed genotypes the predominant aglycon is pelargonidin, and in purple‐fleshed genotypes the most abundant aglycon is petunidin 42 . For the quantification of anthocyanins, a calibration curve was constructed using petunidin‐3‐glucoside as an external standard with the equation y = 101 546 x − 307.4 and the following analytical parameters: DL 0.057 mg L −1 , QL 0.0191 mg L −1 and LR between 0.0191 and 100 mg L −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The structure and content of the secondary metabolites are likely to be affected by cooking because of high temperature (~100 °C). However, cooking of pigmented potatoes still provided valuable levels of phenolic compounds and antioxidant activity independent of temperatures [ 40 , 41 ].…”
Section: Natural Variation and Diversity In Gene Poolsmentioning
confidence: 99%